Sound Quality Ratings of Amplified Speech and Music Using a Direct Drive Hearing Aid: Effects of Bandwidth. Issue 2 (February 2021) - Vaisberg, Jonathan; Folkeard, Paula; Levy, Suzanne; Dundas, Drew; Agrawal, Sumit; Scollie, Susan
Abstract : Objective: To determine sound quality for extended bandwidth amplification using a direct drive hearing device. Study Design: Prospective double-blind within-subjects repeated measures study. Setting: University hearing research laboratories. Patients: Fifteen experienced hearing aid users with symmetric mild-sloping-to-severe sensorineural hearing loss. Intervention(s): Sound quality ratings of speech and music passages were obtained using the Multiple Stimulus with Hidden References and Anchors (MUSHRA) protocol after wearing a direct drive hearing aid for at least 4 weeks. Passages were processed to filter out low-frequency (below 123 and 313 Hz) and high-frequency (above 4455, 5583, 6987, and 10, 869 Hz) energy. Main Outcome Measure(s): Comparison of sound quality ratings for speech and music between low and high-pass filter frequencies measured from 0 to 100, where 0 represents "bad" and 100 represents "excellent." Results: Wider bandwidth stimuli received higher sound quality ratings compared with narrower bandwidth stimuli. Conditions with more low-frequency energy (full-band and 123 Hz cut-off) were rated as having higher sound quality. More low-frequency energy in the 123 Hz condition was rated as having higher sound versus the 313 Hz condition (mean difference: 11.2%, p  = 0.001). Full-band conditions with more low- and high-frequency energy were higher than the other high-frequency cutoff conditions (mean difference range: 12.9–15%, p  < 0.001). Conclusions: The direct drive system provides higher sound quality of both speech and music compared to narrowband conditions. Sound quality improvements were mainly attributable to low-frequency sound, but stimuli with specific high-frequency content were rated with higher sound quality when additional high-frequency energy was present.